Search for an additional, heavy Higgs boson in the $H→ ZZ$ decay channel at $\sqrt{s} = 8\;\text{ TeV }$ in $pp$ collision data with the ATLAS detector - ATLAS collaboration (2853 authors) (2016)
A search is presented for a high-mass Higgs boson in the $H→ ZZ→ \ell ^+\ell ^-\ell ^+\ell ^-$ , $H→ ZZ→ \ell ^+\ell ^-ν \bar{ν }$ , $H→ ZZ→ \ell ^+\ell ^- q \bar{q}$ , and $H→ ZZ→ ν \bar{ν } q \bar{q}$ decay modes using the ATLAS detector at the CERN Large Hadron Collider. The search uses proton–proton collision data at a centre-of-mass energy of 8 TeV corresponding to an integrated luminosity of 20.3 fb$^{-1}$ . The results of the search are interpreted in the scenario of a heavy Higgs boson with a width that is small compared with the experimental mass resolution. The Higgs boson mass range considered extends up to $1~TeV$ for all four decay modes and down to as low as 140 $GeV$ , depending on the decay mode. No significant excess of events over the Standard Model prediction is found. A simultaneous fit to the four decay modes yields upper limits on the production cross-section of a heavy Higgs boson times the branching ratio to $Z$ boson pairs. 95 % confidence level upper limits range from 0.53 pb at $m_{H} =195$ GeV to 0.008 pb at $m_{H} =950$ GeV for the gluon-fusion production mode and from 0.31 pb at $m_{H} =195$ GeV to 0.009 pb at $m_{H} =950$ GeV for the vector-boson-fusion production mode. The results are also interpreted in the context of Type-I and Type-II two-Higgs-doublet models.